Instruments for the promotion of a sustainability oriented management of waste by inter-industrial coordination within an industrial region - Thomas Sterr; Thomas Ott (European Regional Science Association (ERSA), 2002)
The raise of material efficiency is of special importance in the provision of solutions for a more sustainable path of development. One of the main approaches in this direction is the resource saving closure of material circulations among industrial actors. This means at least: maximum rate of recycling combined with a minimum in downgrading processes and spatially close output-input relations - or, in other words: a substantial reduction of social, entropic and spatial distance within the circle-closing process. How can these distances be reduced in order to promote the further spreading of an industrial closed circle economy? What are the present obstacles in the industrial reality and how can they be removed on the level of a firm, an industrial district or an industrial region? These were important questions at the beginning of a research process funded by the Federal Ministry of Education, Science, Research and Technology (BMBF) in order to encourage eco-industrial development in the of Rhine-Neckar region. Taking the results of our close cooperation especially with SME, the problem solving capacity of this industrial region is high enough to close the circles for industrial residues regionally. The dimension of an industrial agglomeration with more than 1,5 million inhabitants could thus already be regarded as a potential output-input system for industrial waste. Nevertheless this capacity is far from being exploited. Taken the fact, that the largest deficiencies were found in the informational situation of SME, two kinds of instruments were developed to facilitate the acquisition and the advantageous usage of waste information by inter-industrial coordination on the level of the industrial region. As informational basis the project coordinators developed a comprehensive, clear and systematic informational structure. A socalled 'AGUM waste manager' was developed as a software tool, that meets all the needs not only for internal information and communication but also for exchanges with potentially fitting output-input partners outside the border of the enterprise. As information on the composition of a certain waste is relatively scarce, the transfer of materials goes together with substantial costs for control, that can only be diminished or substituted by mutual confidence between the two actors. And even a pure informational exchange of waste manager-data between different enterprises would hardly work without a face-to-face contact. Our transparency-guided approach to promote regional sustainability did thus include the development and institutionalisation of an inter-industrial network, that first of all incorporates industrial producers (especially SME) but also other actors, that stand for the problem solving capacity of the region (i.e. universities, political administrations and other institutions) and can thus contribute to the identification and implementation of sustainable-oriented solutions in a regional context.
Keywords: 330